2020
DOI: 10.1038/s41467-020-17696-2
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genetic architectures and environmental factors associate with host response to the γ2-herpesvirus infections

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) and Epstein-Barr Virus (EBV) establish lifelong infections and are associated with malignancies. Striking geographic variation in incidence and the fact that virus alone is insufficient to cause disease, suggests other co-factors are involved. Here we present epidemiological analysis and genome-wide association study (GWAS) in 4365 individuals from an African population cohort, to assess the influence of host genetic and non-genetic factors on virus antibody respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 71 publications
4
25
0
Order By: Relevance
“…More recently, it was also found that EBV infection supports persistent KSHV infection both in humanized mice [ 131 , 134 ] and in vitro [ 130 , 135 ]. Consistent with these findings are the observations that KSHV is usually not found without EBV co-infection in African children [ 136 , 137 ], and that the monkey orthologs of these viruses can be co-transmitted in macaques [ 138 ]. Moreover, co-infection of EBV with KSHV in humanized mice causes increased lymphoma formation, and the emerging lymphomas display some features of plasma cell differentiation [ 131 , 134 ] which is characteristic for PELs [ 133 ].…”
Section: Role Of Co-infections On Ebv Infection Immune Control and Onsupporting
confidence: 57%
“…More recently, it was also found that EBV infection supports persistent KSHV infection both in humanized mice [ 131 , 134 ] and in vitro [ 130 , 135 ]. Consistent with these findings are the observations that KSHV is usually not found without EBV co-infection in African children [ 136 , 137 ], and that the monkey orthologs of these viruses can be co-transmitted in macaques [ 138 ]. Moreover, co-infection of EBV with KSHV in humanized mice causes increased lymphoma formation, and the emerging lymphomas display some features of plasma cell differentiation [ 131 , 134 ] which is characteristic for PELs [ 133 ].…”
Section: Role Of Co-infections On Ebv Infection Immune Control and Onsupporting
confidence: 57%
“…Such coinfection can also be observed in primary effusion lymphoma (PEL), a B cell tumor in which KSHV genome maintenance is compromised when EBV is deleted [21,22]. Furthermore, epidemiologically, KSHV infection is associated with EBV infection in African children [23,24]. It remains unclear under which circumstances KSHV infects the endothelial cells from which Kaposi sarcoma originates [2,25].…”
Section: Human γ-Herpesvirus Infections and Associated Pathologiesmentioning
confidence: 99%
“…Both EBV and KSHV are found in the tumor cells of 90% of primary effusion lymphomas (PELs) ( 10 ). Moreover, KSHV infection seems to benefit from EBV co-infection for persistence ( 47 , 86 88 ). Humanized mice that are infected with both KSHV and EBV develop B cell lymphomas with higher incidence ( 47 ).…”
Section: Alteration Of Ebv Associated Pathogenesis By Co-infectionmentioning
confidence: 99%